2022
DOI: 10.1039/d2cc03766a
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte/surfactant films: from 2D to 3D structural control

Abstract: Reversible control of the 3D structure of polyelectrolyte/surfactant films at the air/water interface is showcased. A recently discovered mechanism is exploited to form highly efficient, stable and biocompatible films by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…Recent research indicated that stable aqueous dispersions of PE/AlS aggregates, i.e., dispersed microphases of the coacervate phase, could be prepared [33][34] with various supramolecular structures [35][36] . These aggregates may adsorb or be transferred directly to the air/water or oil/water interfaces where they resemble the behavior of insoluble multilayers [37][38][39] in agreement with the hindered desorption of the surfactant ions bound to oppositely charged polyelectrolytes. [40][41] Furthermore, the redispersion of the bulk coacervate may be used to prepare stable emulsions, with PE/AlS aggregates acting as Pickering particles.…”
Section: Introductionmentioning
confidence: 71%
“…Recent research indicated that stable aqueous dispersions of PE/AlS aggregates, i.e., dispersed microphases of the coacervate phase, could be prepared [33][34] with various supramolecular structures [35][36] . These aggregates may adsorb or be transferred directly to the air/water or oil/water interfaces where they resemble the behavior of insoluble multilayers [37][38][39] in agreement with the hindered desorption of the surfactant ions bound to oppositely charged polyelectrolytes. [40][41] Furthermore, the redispersion of the bulk coacervate may be used to prepare stable emulsions, with PE/AlS aggregates acting as Pickering particles.…”
Section: Introductionmentioning
confidence: 71%
“…These differences may be related to the ability of the polyelectrolyte to wrap surfactant aggregates, which would be significantly influenced by its stiffness, [55][56][57] and it has also been found that more rigid polyelectrolytes form denser films. 7 Thus, the experimental charge neutrality may be an important parameter when assessing the stability of formed ESs in P/S or PP/S films, given that they were shown to be stable over time for PLL/SDS films with strong bulk binding 27 and unstable for NaPSS/DTAB films with weaker bulk binding. 31 Furthermore, it has been recently demonstrated that the rigidity of the polymer plays an important role in the stabilization of ESs in adsorbed layers in mixed P/S systems.…”
Section: Resultsmentioning
confidence: 99%
“…31 Bulk SDS concentrations of 0.80 and 0.62 mM were chosen to create the spread PLL/SDS and PLA/SDS films, respectively, because aggregates overcharged with an excess of surfactant have been shown to be efficient in forming ESs in previous studies. 27,31 It is worth noting that the release of counterions to the bulk results in a very dilute electrolyte concentration (∼30 μM) that is not expected to influence the spread film properties significantly. Indeed, spread films of the NaPSS/DTAB system exhibit persistent loss of material over time at elevated ionic strength of 100 mM, 31 for which there is no evidence from the ellipsometry data of either PP/S system in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This redistribution process, however, resulted in gradual changes in the size, charge distribution, and structure of the polyelectrolyte/surfactant nanoassemblies. This phenomenon was attributed to the largely reduced mobility of the surfactant ions bound to the oppositely charged polyions. , …”
Section: Introductionmentioning
confidence: 99%